MARKETING MIX 7P DIBALIK SUKSESI KREATIF BISNIS KULINER BERTEMA ETNIK SEOUL PALACE SEMARANG (7P-Marketing Mix Behind The Creative Succession of Culinary Business with Ethnic Theme in Seoul Palace Semarang) - Heni Krisnatalia (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
This study aims to determine the effect of 7P-Marketing Mix Elements (Product, Price, Place, Promotion, People, Process, and Physical Evidence) on the "Seoul Palace" Semarang Restaurant to identify the concept of an ethnic-themed restaurant and to analyze it based on a study using a qualitative descriptive approach , carried out through observation, interview with restaurant managers, and documentation. Based on the research carried out on the concept of an ethnic-themed restaurant, it can be stated that there are 3 basic aspects supporting the restaurant's existence, including an atmosphere that is characterized by ethnicity, especially Korea in accordance with the theme it carries as an attraction to its visitors. The quality of the product is maintained with a variety of selected imported ingredients to produce the taste of ethnic dishes. Guidelines “first-come, first-served visitors always” puts first-arriving visitors first. Meanwhile, the results of the 7P marketing mix of products, in terms of product itself, its quality, brand, packaging, label, and type of product have been fully fulfilled, pricing is measured by the cost of competing products through cost-based pricing, with a variety of payment systems offered from the cost of competing products, strategic choice of place and supported by word of mouth promotion, publicity, to sales promotion with human resources (people) understanding the menu and cooking procedures for Korean food. The process (the process) offers open kitchen facilities and self-service cooking which is a series of physical evidence replete with supporting factors.